Intention to Donate on Online Charitable Crowdfunding: Systematic Literature Review and Future Research Agenda - Putu Laksmita Dewi Rahmayanti; I Ketut Rahyuda; Ni Wayan Ekawati; Putu Yudi Setiawan (Universitas Hayam Wuruk Perbanas, 2025)
The effectiveness of online charitable crowdfunding is contingent upon the contributions made by donors. Given the significance and relevance of this topic, the primary objective of this research is to identify, examine, and provide a framework for understanding the intentions of donors who contribute to online charitable crowdfunding platforms. The literature search was conducted by PRISMA guidelines. Keyword searches were conducted in the Scopus and Science Direct databases until July 2023. The inclusion and exclusion criteria for the retrieved research yielded 34 papers. The study’s findings indicate that UTAUT and SOR exhibit the most prevalent occurrences. The technical and behavioral aspects are of utmost significance. Intrinsic motivation is driven by various factors such as empathy, trust, compassion, attitude, morality, and self-worth. The extrinsic factors include social influence, literacy, and perceived behavioral control. Given the results mentioned earlier, it is appropriate to draw a conclusion and propose avenues for future investigation. The study contributes to the theoretical understanding of online charitable crowdfunding by identifying and analyzing the factors influencing donor intentions. The study highlights the significance of both intrinsic and extrinsic motivations, expanding the theoretical framework to encompass diverse factors such as empathy, trust, morality, and social influence.